Exploring the central region of amylin and its analogs aggregation: the influence of metal ions and residue substitutions - Alghrably, Mawadda; Bennici, Giulia; Szczupaj, Gabriela; Alasmael, Noura; Qutub, Somayah; Maatouk, Batoul; Chandra, Kousik; Nowakowski, Michal; Emwas, Abdul-Hamid; Jaremko, Mariusz (Frontiers in Chemistry, 2024)
Human amylin (hIAPP) is found in the form of amyloid deposits within the pancreatic cells of nearly all patients diagnosed with type 2 diabetes mellitus (T2DM). However, rat amylin (rIAPP) and pramlintide - hIAPP analogs - are both non-toxic and non-amyloidogenic. Their primary sequences exhibit only slight variations in a few amino acid residues, primarily concentrated in the central region, spanning residues 20 to 29. This inspired us to study this fragment and investigate the impact on the aggregation properties of substituting residues within the central region of amylin and its analogs. Six fragments derived from amylin have undergone comprehensive testing against various metal ions by implementing a range of analytical techniques, including Nuclear Magnetic Resonance (NMR) spectroscopy, Thioflavin T (ThT) assays, Atomic Force Microscopy (AFM), and cytotoxicity assays. These methodologies serve to provide a thorough understanding of how the substitutions and interactions with metal ions impact the aggregation behavior of amylin and its analogs.